2004
DOI: 10.1593/neo.03343
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Water Mobility Measured by Diffusion MRI Predict Response of Metastatic Breast Cancer to Chemotherapy

Abstract: The goal of oncology is the individualization of patient care to optimize therapeutic responses and minimize toxicities. Achieving this will require noninvasive, quantifiable, and early markers of tumor response. Preclinical data from xenografted tumors using a variety of antitumor therapies have shown that magnetic resonance imaging (MRI)-measured mobility of tissue water (apparent diffusion coefficient of water, or ADCw) is a biomarker presaging cell death in the tumor. This communication tests the hypothesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
161
1
4

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 228 publications
(177 citation statements)
references
References 21 publications
11
161
1
4
Order By: Relevance
“…Our preliminary experience in primary and metastastic liver cancers suggests early increases in tumour mean ADC are correlated with eventual response to radiation treatment and is in keeping with the results of others [3,10,12,13]. When compared to baseline, the greatest early increase in tumour mean ADC was seen during the first week of RT.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Our preliminary experience in primary and metastastic liver cancers suggests early increases in tumour mean ADC are correlated with eventual response to radiation treatment and is in keeping with the results of others [3,10,12,13]. When compared to baseline, the greatest early increase in tumour mean ADC was seen during the first week of RT.…”
Section: Discussionsupporting
confidence: 89%
“…Other authors have seen increases in ADC as early as 4Á11 days post start of anti-cancer treatments [10,11,13]. Theilman et al investigated the relationship between lesion sizes at baseline with response predicted by changes in mean ADC [10]. There was a trend towards smaller lesions having larger changes in ADC, similar to our findings.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…[15][16][17][18] It is reported that following radiotherapy, ADCs may rapidly decrease over several hours owing to cell swelling, followed by an increase over several days with concurrent cell death. 19,20 When compared with baseline, the greatest early increase in tumour mean ADC values was seen during the first week of radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…The usefulness of DWI has been demonstrated both in detection and in characterization of focal hepatic lesions (1,3,4). The value of DWI for monitoring the response to different types of tumor treatment is currently being investigated extensively (5)(6)(7)(8)(9).…”
Section: Methodsmentioning
confidence: 99%